Targeted hydrolysis of native potato protein: A novel workflow for obtaining hydrolysates with improved interfacial properties. (April 2023) - Gregersen Echers, Simon; Jafarpour, Ali; Yesiltas, Betül; García-Moreno, Pedro J.; Greve-Poulsen, Mathias; Hansen, Dennis K.; Jacobsen, Charlotte; Overgaard, Michael Toft; Hansen, Egon Bech
Abstract: Peptides and protein hydrolysates are promising alternatives to substitute chemical additives as functional food ingredients. In this study, we present a novel workflow for producing a potato protein hydrolysate with improved emulsifying and foaming properties using quantitative proteomics and bioinformatic prediction to facilitate targeted hydrolysis design. Based on previous studies, we selected 15 potent emulsifier peptides derived from abundant potato proteins as targets. Through in silico analysis, we determined that from a range of industrial proteases (Neutrase (Neut), Alcalase (Alc), Flavourzyme (Flav) and Trypsin (Tryp)), Tryp was found more likely to release peptides resembling the targets. After applying all proteases individually, hydrolysates were assayed for in vitro emulsifying and foaming properties. No direct correlation between degree of hydrolysis and interfacial properties was found. Tryp (E/S = 3%) produced a hydrolysate (DH = 5.4%) with high aqueous solubility and the highest (P < 0.05) emulsifying and foaming abilities, validating the hypothesis. Using LC-MS/MS, we identified >10, 000 peptides in each hydrolysate. Peptide mapping revealed that random overlapping with known peptide emulsifiers is not sufficient to quantitatively describe hydrolysate functionality. However, validated release of targeted peptides by 3% Tryp appears to increase surface activity of the hydrolysate. Our data also suggest that terminal hydrophobic anchor domains may be important for high interfacial partitioning and activity. While modest yields and residual unhydrolyzed protein indicate room for process improvement, this work shows that bioinformatics-guided and data-driven targeted hydrolysis is a promising, interdisciplinary approach to facilitate process design for production of functional hydrolysates from alternative protein sources. Graphical abstract: Image 1 Highlights: A novel data-driven workflow for targeted hydrolysis of potato protein is presented. As predicted, tryptic hydrolysates were better (P < 0.05) emulsifiers of fish oil. More than 10, 000 peptides were identified in each hydrolysate investigated. Trypsin released target peptides, correlating with improved interfacial properties. Overlap with known emulsifiers was insufficient for describing emulsifying ability.